Analysis of the Management Decision-Making Process Based on Predictive Analytics in Projecting PT Telkom (Persero) Tbk. Ability to Meet Long-Term Financial Obligations - Raihan Fauzan Adim; Agustina Septiana; Muhamad Nur Amin; Fabio Alfarabi Putra; Asri Sundari (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study analyzes the solvency of PT Telkom Indonesia (Persero) Tbk and assesses the adequacy of documentary evidence regarding the use of predictive analytics in financial decision-making. Research Method: This study employs a descriptive case study approach with a documentary analysis of the audited consolidated financial statements for 2025 and the restated comparative figures for 2024. The analysis covers the liability structure, profitability, free cash flow, lease-adjusted leverage, net debt, and cost of capital coverage. Results and Discussion: Long-term liabilities increased by 4.72%, while operating income decreased by 16.42% and the TIER proxy fell from 7.96 to 6.66 times. Conversely, operating cash flow increased by 3.64%, net financial debt decreased, and the debt-to-equity ratio (DER), adjusted for leases, remained relatively stable at 49.76%. The analyzed document does not provide specifications or validation of the predictive model; therefore, the effectiveness of its implementation cannot be concluded. Implications: Solvency assessments need to use multidimensional indicators and verifiable disclosures regarding model governance. Originality: This study identifies the empirical boundary between descriptive financial analysis and predictive analytics in assessing the solvency of telecommunications companies.